A Bibliometric Analysis and Visualisation of Research Trends in Toxicity of knee Implants (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Several metals are used for Knee implants. Toxicity of metals may lead to toxicity of knee implants. This bibliometric analysis had been conducted to understand the active authors, organizations, journals, and countries involved in the research domain of “toxicity of knee implants”. All published articles related to “toxicity of knee implants” from “Scopus”, were analyzed using the VOS viewer to develop analysis tables and visualization maps. This article had set the objective to consolidate the scientific literature regarding “toxicity of knee implants” and also to find out the trends related to the same. The most active journal in this research domain was Biomaterials. The most active country was the United States of America. The leading organization engaged in research regarding the toxicity of knee implants were the Indian Institute of Science, Bengaluru, India, University of Leeds, United Kingdom, and the Beihang University of China. The most active authors were Hallab N.J. and Jacobs J.J.